Literacy and Numeracy Skills and Life-Course Outcomes: Evidence from PIAAC and Linked Administrative Data - Meehan, Lisa; Pacheco, Gail; Schober, Thomas (Australian Journal of Labour Economics (AJLE), 2024)
This paper examines the life-course trajectories of NZ adults across different literacy and numeracy skill levels. This is done by using skill information for the working-age adult population (aged 16-65 years) collected in the Survey of Adult Skills (PIAAC). This sample is then linked with administrative data to track their life-course outcomes from 2008 to 2020. The outcomes of the one-fifth of NZ working-age adults who were assessed at below Level 2 in either literacy or numeracy (or both) are compared with those at or above this baseline. It finds that adults with low measured skills have less favourable outcomes in a number of areas. They have lower rates of educational attainment, lower employment rates and average earnings, higher rates of hospitalisation, and higher rates of criminal offending and convictions. In addition, outcomes for Māori and Pacific peoples in both the low-skills and above-baseline groups are generally less favourable than those of their NZ European counterparts. For example, even among those with above-baseline skills, Māori and Pacific peoples have lower average earnings than NZ Europeans. These results provide a quantifiable evidence base regarding the role of literacy and numeracy skills with respect to a range of wellbeing outcomes over the course of an individual’s life.
Keywords: 1402 Applied Economics; 1403 Econometrics; 1605 Policy and Administration; 3801 Applied economics; 4407 Policy and administration